(untitled) (Nigerian Journal of Pharmaceutical Research, 2022)
Background: The increase in the worldwide prevalence and resistance of organisms causing urinary tract infections (UTIs) to the conventional antibiotics used in treatment has led to sub-therapeutic outcome, hence, the need to discover novel antibiotics from natural products. Ficus mucuso Welw. and Ficus vogelii Miq. have been used in ethnomedicine for the treatment of diseases of microbial origin. Objective: To investigate the antimicrobial activity of Ficus vogelii and Ficus mucuso leaf extracts and fractions against UTI clinical isolates. Materials and Method: The pulverized leaves of plants were screened for secondary metabolites. Crude extracts were obtained by maceration with methanol and partitioned into methanol, ethyl acetate and n- Hexane. Antibiogram profile of clinical isolates; Escherichia coli, Proteus vulgaris, Serratia marcescens, Salmonella Typhi , Pseudomonas aeruginosa, Providencia stuartii, Klebsiella pneumoniae and Staphylococcus aureus was determined using disc diffusion method. Antimicrobial activities of the leaf extracts and fractions of both plants were screened by agar-well diffusion. Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were determined by micro-dilution broth assay. Results: The phytochemical screening revealed the presence of terpenoids, steroids, anthraquinones, alkaloids, tannins, flavonoids, saponin. The antibiogram profile showed that 87.5% of the isolates were multidrug resistant. Extracts and fractions showed appreciable inhibitory zones on most of the test organisms. MIC ranged from 6.25 - 25 mg/mL while MBC ranged from 50 - >100 mg/mL with ethyl acetate fraction of Ficus mucuso having the highest bactericidal activity against the isolates. Conclusions: Extracts of Ficus mucuso and Ficus vogelii possess antimicrobial constituents which could be useful in the treatment of UTIs.